2020
DOI: 10.1002/ijfe.2072
|View full text |Cite
|
Sign up to set email alerts
|

Bank deposits and Google searches in a crisis economy: Bayesian non‐linear evidence for Greece (2009–2015)

Abstract: Due to a variety of reasons, the Greek economy faced a severe crisis being a member of EMU. Nonetheless, the country's banking system experienced a dramatic outflow of deposits, in the period 2009–2015. The present paper attempts to shed light on the possibility of forecasting bank deposits, based on the keyword “Grexit” of Google searches. In this context, apart from standard forecasting models like AR (p) and ARDL (p, q) we estimate a novel Neural Network ARDL (p, q, G) model and its respective Bayesian modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…In a similar vein, Konstantakis et al. (2021) found that intensified Google searches containing the keyword “Grexit”, which summarize the public sentiment about the situation of the Greek economy, significantly affect depositors' perceptions and, ultimately their behavior regarding whether to withdraw their deposits or not. Lastly, Anastasiou and Drakos (2021), by introducing two modified Google search‐based crisis sentiment metrics of depositors' aggregate level of crisis sentiment, documented that depositors' crisis sentiment is related to irrational behavior and is negatively associated with bank deposit flows.…”
Section: Review Of the Literaturementioning
confidence: 93%
See 2 more Smart Citations
“…In a similar vein, Konstantakis et al. (2021) found that intensified Google searches containing the keyword “Grexit”, which summarize the public sentiment about the situation of the Greek economy, significantly affect depositors' perceptions and, ultimately their behavior regarding whether to withdraw their deposits or not. Lastly, Anastasiou and Drakos (2021), by introducing two modified Google search‐based crisis sentiment metrics of depositors' aggregate level of crisis sentiment, documented that depositors' crisis sentiment is related to irrational behavior and is negatively associated with bank deposit flows.…”
Section: Review Of the Literaturementioning
confidence: 93%
“…Many prior studies Drakos, 2020, 2021;Forssbaeck, 2011;Hasan et al, 2013;Konstantakis et al, 2021;Oliveira et al, 2011), have found that depositors exhibit low sensitivity to the bank or macro-specific fundamentals, with the effect being more prominent during crisis periods. Similarly, Hosono (2005) demonstrated that in South Korea, Malaysia, and Thailand, the sensitivity of deposit volumes to bank fundamentals declined after 1998.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this regard, a question arises: Why should we choose a country like Greece to apply this research? In this respect, in the last 10 years Greece has experienced a sovereign debt crisis, a bank-run and currently the pandemic (Featherstone 2011 ; Mink and De Haan 2013 ; Konstantakis et al 2021 ). The debt crisis led to a fiscal consolidation for almost 8 years, the banking crisis called for the imposition of capital controls in domestic and international capital flows, and the health crisis imposed a lockdown in almost all sectors in the Greek economy.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that these textual sentiments have a more significant impact on non-financial corporations than households. Konstantakis, Paraskeuopoulou, Michaelides, and Tsionas (2020) showed that extending standard autoregressive models with the keyword "Grexit" leads to improvement in the forecasting ability of the Bank Deposits in Greece, compared to models that contain just some standard explanatory variables. Their findings are checked for robustness in the data samples, in the activation function used and the prior distributions employed and are found to be econometrically robust and economically sound, confirming the crucial role of Google Searches for predicting bank deposits in the Greek economy.…”
Section: Introductionmentioning
confidence: 99%